Yoga for dummies - Payne, Larry; Feuerstein, Georg (--For dummies., 2014)
Learn the safe and easy way to benefit from the practice of yoga. Payne ande Feuerstein help you design and follow your own personal program in order to achieve your fittest, healthiest, happiest self.